Translation and validation of diabetes self-management profile (DSMP) into Brazilian Portuguese language: first instrument to assess type 1 diabetes self-management in a pediatric population - Passone, Caroline Gouveia Buff (Diabetol Metab Syndr, 2017)
OBJECTIVE: To translate and validate the instrument Diabetes Self-Management Profile (DSMP)—Conventional and Flexible Regimens into Brazilian Portuguese language in order to evaluate the quality of diabetes self-management in children and adolescents with type 1 diabetes and their caregivers. METHODS: DSMP was submitted to forward and back translation method and validated in a group of type 1 diabetes youths between 6 and 18 years (n = 102), and their families. Analysis of DSMP internal consistency, intra and interobserver reliability and concurrent correlation with HbA1c were done. RESULTS: DSMP total scores demonstrated adequate internal consistency (Cronbach’s α = 0.79), 3-month test–retest reliability (ρ = 0.53; p < 0.001), inter-interviewer agreement (ρ = 0.55; p < 0.001). DSMP total score was significantly correlated to HbA1c (ρ = −0.54, p < 0.001). CONCLUSION: DSMP-translated version is a reliable and valid tool to assess diabetes self-management.